Evaluation of side effect of risperidon on schizophrenic patient in Amino Gondohutomo hospital Semarang - M. Caecilia N Setiawati; Nanang Munif Yasin; Septiana Laksmi R (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Schizophrenia is a psychiatrical chronical disease of human being’s mind which can influence someone so that it bothered the interpersonal relation and ability to have a social relationship. Antipsychotic drug can be used to overcome the symptom of schizophrenia, for example risperidone. This study was aims to evaluate the side effects of the use of risperidoneon the inpatient of Dr. Amino Gondohutomo Mental Hospital Semarang for a month in the period of February 2008. This evaluation covers the side effects of medicine that occur due to the use of risperidone, concomitant administration of risperidone and other antipsychotic, drug interaction,and also executed therapy of the side effects of the risperidone. This study followed the descriptive analysis, while the data collecting was conducted prospectively. The subjects of research were represented by the entire patients of the inpatient ward of Dr. Amino Gondohutomo Mental Hospital Semarang during the period of February 2008 and fulfilled the inclusive criteria. The inclusive criteria covered the patients who were diagnosed as paranoid schizophrenia, hebephrenic schizophrenia, catatonic schizophrenia, undetailed schizophrenia and received anti-psychotic risperidone medication. Based on these criteria 31 samples were found. The result of the study indicated that the most possibility of side effects of the use of risperidone was agitation (19.51 %), with the most anti-psychotic combination of risperidone and haloperidol (45.83 %) and there were 15 interactions which could potentially cause a drug side effect.Key words: schizophrenia, drug side effects, anti-psychoticrisperidone